Effect of growth regulators on PLBs and shoot multiplication in hybrid orchid - Ahmed, MF; Khatun, M; Kabir, MH; Mony, SA; Huda, MN (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 19-24